2019
DOI: 10.5812/iranjradiol.78775
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Between Transudative and Exudative Pleural Effusions by Diffusion Weighted Magnetic Resonance Imaging

Abstract: Background: Pleural effusion could develop in very different pathological conditions. It is important to characterize pleural effusion and to identify its etiology. Different radiological methods, such as ultrasonography (US), computed tomography (CT) and magnetic resonance imaging (MRI) are used for the diagnosis of pleural effusion. Objectives: To assess the ability of diffusion weighted imaging and apparent diffusion coefficient (ADC) maps to differentiate transudative effusions (TEs) from exudative effusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…CEUS has shown promising results in distinguishing between benign and malignant pleural lesions based on their vascularity patterns [40]. On the other hand, DW-MRI has demonstrated potential in detecting and characterizing MPE, particularly when CT findings are inconclusive [41]. Furthermore, integrating imaging findings with other diagnostic modalities, such as thoracoscopy, pleural fluid analysis, and molecular biomarkers may further enhance the diagnostic accuracy and management of MPE [42].…”
Section: Discussionmentioning
confidence: 99%
“…CEUS has shown promising results in distinguishing between benign and malignant pleural lesions based on their vascularity patterns [40]. On the other hand, DW-MRI has demonstrated potential in detecting and characterizing MPE, particularly when CT findings are inconclusive [41]. Furthermore, integrating imaging findings with other diagnostic modalities, such as thoracoscopy, pleural fluid analysis, and molecular biomarkers may further enhance the diagnostic accuracy and management of MPE [42].…”
Section: Discussionmentioning
confidence: 99%
“…The ADC map obtained by DWI has emerged as a new method for characterization of pleural fluid at the molecular level [27]. There are 3 studies in the English language medical literature regarding the use of DWI in pleural fluid analysis [27][28][29]. In these studies, the ADC values were found to be lower in the exudative fluids than in the transudative fluids.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, only the ADC values of the fluids were taken into consideration, while a quantitative and qualitative analysis of the DWI was not performed. The ADC threshold value, specificity, sensitivity, NPV, PPV, and diagnostic accuracy ratio were 3/38 × 10 -3 mm 2 /s, 85%, 90.6%, 85%, 90.6%, and 88.5% for the first study; 3.6 × 10 -3 mm 2 /s, 63%, 71%, 68%, 66%, and 67% for the second study; and 3.51 × 10 -3 mm 2 /s, 90.4%, %78, 86.5%, 83.9%, and 84.9% for the third study [ 26 , 28 , 29 ]. In the present study, the ADC threshold value was measured as 2.95 × 10 -3 mm 2 /s, and the threshold value was significantly lower than in the other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The ADC values represent a quantitative measurement of the degree of such motion in tissue, and are also used as a marker of cellularity [15]. Aside from being a noninvasive, reliable, and reproducible imaging parameter, the ADC measurements have been proven to be useful in the evaluation and characterization of different types of effusion [15,17]. To our knowledge, research involving these methods has been limited to the pleural fluid to date, and successfully proved that differences in liquid content have an important influence on ADC values [16][17][18].…”
Section: Discussionmentioning
confidence: 99%